1999
DOI: 10.1111/1468-0394.00107
|View full text |Cite
|
Sign up to set email alerts
|

The rise and ‘fall’ of expert systems in medicine

Abstract: This paper represents a personal perspective on the last 13 years of research in medical artificial intelligence and expert systems, and describes the progress of the discipline from its inception to its current status. The challenges faced by researchers are examined, and it is argued that (despite the claims) theoretical and technical limitations are not the major barriers to the successful implementation of medical artificial intelligence and expert systems, but rather more complex professional and organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 35 publications
(40 reference statements)
0
23
0
1
Order By: Relevance
“…When hospital information systems were first introduced, it was found that the greatest difficulties in their deployment lay not with technical issues but with the end-users, on whom new demands were being placed (Harrison, 1991). Recent health informatics research also reveals that social and organizational factors can determine the success or failure of healthcare IT developments (Harrison, 1991;Heathfield, 1999). Heathfield (1999) suggests that this is due to the complex, autonomous nature of the medical discipline and the specialized approaches to system development (which are typically led by either a clinician or a software engineer).…”
Section: Communities Of Practice and The Clinical Domainmentioning
confidence: 99%
See 1 more Smart Citation
“…When hospital information systems were first introduced, it was found that the greatest difficulties in their deployment lay not with technical issues but with the end-users, on whom new demands were being placed (Harrison, 1991). Recent health informatics research also reveals that social and organizational factors can determine the success or failure of healthcare IT developments (Harrison, 1991;Heathfield, 1999). Heathfield (1999) suggests that this is due to the complex, autonomous nature of the medical discipline and the specialized approaches to system development (which are typically led by either a clinician or a software engineer).…”
Section: Communities Of Practice and The Clinical Domainmentioning
confidence: 99%
“…Recent health informatics research also reveals that social and organizational factors can determine the success or failure of healthcare IT developments (Harrison, 1991;Heathfield, 1999). Heathfield (1999) suggests that this is due to the complex, autonomous nature of the medical discipline and the specialized approaches to system development (which are typically led by either a clinician or a software engineer). The diverse organizational culture of hospital structures, made up of many different professions with their own specific social identifiers, can often produce conflicts between those professions (Morgan, 1991).…”
Section: Communities Of Practice and The Clinical Domainmentioning
confidence: 99%
“…Users therefore need support in obtaining a shared understanding of corporate perspectives and establishing productive collaborations across an organization. This is especially true within the clinical domain where the complex, autonomous and hierarchical nature of the medical discipline can isolate users from organizational issues [1].…”
Section: Health Informatics Journalmentioning
confidence: 99%
“…When hospital information systems were first introduced, it was found that the greatest difficulties in deployment lay not with technical issues but with the users, through their reactions to systems introduction and the demands of acquiring new skills [26]. Recent health informatics research also reveals that social and organizational factors can determine the success or failure of healthcare IT developments [1,27,28]. Negative reactions to these systems are often due to inappropriate system design and poor implementation.…”
Section: Clinical Domain and Communities Of Practicementioning
confidence: 99%
See 1 more Smart Citation